2022
DOI: 10.1002/chem.202104041
|View full text |Cite
|
Sign up to set email alerts
|

Coordination‐Induced Band Gap Reduction in a Metal–Organic Framework

Abstract: Herein, we report on the synthesis of a microporous, three‐dimensional phosphonate metal–organic framework (MOF) with the composition Cu3(H5‐MTPPA)2 ⋅ 2 NMP (H8‐MTPPA=methane tetra‐p‐phenylphosphonic acid and NMP=N‐methyl‐2‐pyrrolidone). This MOF, termed TUB1, has a unique one‐dimensional inorganic building unit composed of square planar and distorted trigonal bipyramidal copper atoms. It possesses a (calculated) BET surface area of 766.2 m2/g after removal of the solvents from the voids. The Tauc plot for TUB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
0
6
1
Order By: Relevance
“…Hypothetically, the use of narrow band gap or semiconducting MOFs might help improve OER kinetics, and currently there is a limited number of narrow band gap MOFs in the literature [40] . Our research group has recently reported on the electrical conductivity of microporous phosphonate MOFs and layered metal phosphonates [17,20,41–44] . The reported semiconducting phosphonate MOFs by our group have narrow band gaps between 1.4 and 2.5 eV.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Hypothetically, the use of narrow band gap or semiconducting MOFs might help improve OER kinetics, and currently there is a limited number of narrow band gap MOFs in the literature [40] . Our research group has recently reported on the electrical conductivity of microporous phosphonate MOFs and layered metal phosphonates [17,20,41–44] . The reported semiconducting phosphonate MOFs by our group have narrow band gaps between 1.4 and 2.5 eV.…”
Section: Introductionmentioning
confidence: 80%
“…[40] Our research group has recently reported on the electrical conductivity of microporous phosphonate MOFs and layered metal phosphonates. [17,20,[41][42][43][44] The reported semiconducting phosphonate MOFs by our group have narrow band gaps between 1.4 and 2.5 eV. We have previously shown that changing the identity and coordination environment of the metal ions in isostructural MOFs and hydrogen-bonded organic framework (HOFs) are important tools for fine band-gap tuning of the framework.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphonate-MOFs (MOFs = metal-organic frameworks) have recently been a very active research area, especially with respect to the exceptional thermal and chemical stabilities of phosphonate-MOFs. [1][2][3][4][5][6] The recent developments in phosphonate-MOFs have paved a way to several breakthroughs and generated novel stable microporous materials exhibiting magnetic, semiconducting, and proton conducting properties, and they found further applications in electrocatalysis and photocatalysis. [3,[7][8][9][10][11] The activity in phosphonate MOF research have been documented by many review articles that have been published during the last five years.…”
Section: Introductionmentioning
confidence: 99%